Street adolescents in low income setting exposed to hepatitis B and C, and disadvantaged by lifestyle: a Togolese cross-sectional study - Arnold Junior Sadio; Valentine Marie Ferré; Oumarou I. Wone Adama; Harold Régis Kouanfack; Anoumou Claver Dagnra; Amivi P. Amenyah-Ehlan; Laté Mawuli Lawson-Ananissoh; Diane Descamps; Charlotte Charpentier; Didier Koumavi Ekouevi (BMC, 2024)
Abstract Background In Togo, few data are available on viral hepatitis in street adolescents, a vulnerable population due to their lifestyle. The aim of this study was to describe the lifestyle of street adolescents (sexual practices and drug use), to estimate the prevalence of hepatitis B and C viruses, and to describe their HBV immunization profile in Togo. Methods A cross-sectional study was conducted in Lomé (Togo) in July 2021. Street adolescents aged between 13 and 19 years were included. A questionnaire was used to document lifestyle. ELISA tests were performed for Hepatitis B surface antigen (HBsAg), Hepatitis B core and surface antibodies (anti-HBc, anti-HBs), and antibodies against hepatitis C virus (anti-HCV). Results A total of 299 adolescents (5.4% female) with a median age of 15 years (IQR: 14-17) were included. Of these, 70.6% (211/299) were sexually active and 70.6% (149/211) had not used a condom during their last sexual intercourse. Drug use was reported by 42.1% of the adolescents. The most used substances were cannabis (39.0%), cocaine (36.6%), glue solvents (19.5%), and tramadol (11.4%). However, cocaine use may have been overestimated due to information bias. Current HBV infection (HBsAg+) was detected in 3.7% (95%CI: 1.9-6.5) of the adolescents. Isolated anti-HBc + was present in 5.3%. All three HBV markers (HBsAg, anti-HBs, and anti-HBc) were negative in 71.6% of adolescents. Anti-HCV was detected in 4.7% of adolescents. Conclusion Nearly one in 10 street adolescents has markers for HBV contact/current infection, and approximately 72% of street adolescents may still be infected with HBV, as they have no HBV markers. HCV is also circulating in this population. Given the reported high-risk sexual practices and high levels of drug use, there is an urgent need to develop integrated strategies to prevent infections, including HBV, and drug dependence in this population.